Occurrence of Plasmid-Mediated AmpC β-Lactamases Among Escherichia coli and Klebsiella pneumoniae Clinical Isolates in a Tertiary Care Hospital in Bangalore - Sasirekha, B. (Springer-Verlag, 2011)
Therapeutic options for infections caused by gram-negative organisms expressing plasmid-mediated AmpC β-lactamases are limited because these organisms are usually resistant to all the β-lactam antibiotics, except for cefepime, cefpirome and the carbapenems. These organisms are a major concern in nosocomial infections and should therefore be monitored in surveillance studies. Hence, this study was aimed out to determine the prevalence of plasmid-mediated AmpC β-lactamases in E. coli and K. pneumoniae from a tertiary care in Bangalore. A total of 63 E. coli and 27 K. pneumoniae were collected from a tertiary care hospital in Bangalore from February 2008 to July 2008. The isolates with decreased susceptibility to cefoxitin were subjected to confirmation test with three dimensional extract tests. Minimum inhibitory concentrations (MICs) were determined by agar dilution method. Conjugation experiments, plasmid profiling and susceptibility testing were carried out to investigate the underlying mechanism of resistance. In our study, 52 (57.7%) isolates showed resistance to cefoxitin, the occurrence of AmpC was found to be 7.7% of the total isolates. Plasmid analysis of the selected isolates showed the presence of a single plasmid of 26 kb in E. coli and 2 Kb in K. pneumoniae. Plasmid-mediated AmpC β-lactamases were found in 11.1% of K. pneumoniae and in 6.3% of E. coli. Curing and conjugation experiments showed that resistance to cephamycins and cephalosporins was plasmid-mediated. Our study has demonstrated the occurrence of plasmid-mediated AmpC in E. coli and K. pneumoniae which illustrates the importance of molecular surveillance in tracking AmpC-producing strains at general hospitals and emphasizes the need for epidemiological monitoring.